Searching for clusters with SUMSS - Buttery, H; Cotter, G; Hunstead, R; Sadler, E (2003)
Searches for statistical overdensities of radio sources in the NRAO VLA Sky Survey (NVSS) survey have led to the detection of high redshift clusters of galaxies (Cotter et al. 2002; Croft et al. 2001). We have carried out a similar search for overdensities using the Sydney University Molonglo Sky Survey (SUMSS). Radio observations at 20/13 cm have been made of these candidates at the Australia Telescope Compact Array (ATCA) revealing sources of diffuse cluster emission as well as groups of FR1 sources showing structures associated with clusters, indicating a cluster "hit-rate" of about 70%.